Spatial Distribution of Economic Activities in Local Labour Market Areas: the Case of Italy - Giuseppe Arbia; Laura De Dominicis; Henri L.F. De Groot (European Regional Science Association (ERSA), 2006)
In recent years, a large number of studies investigated the spatial distribution of economic activities in Western Europe by means of various measures of geographical concentration. The fundamental problem with the indices currently used in the literature is that they do not take explicitly into account the spatial structure of the data, and as a result the same degree of concentration is compatible with very different localization schemes. In the present work we present an analysis which combines the information provided by the standard measure of concentration of Ellison and Glaeser together with the measure of spatial correlation introduced by Moran. The problem known in geography as MAUP is here addressed by considering both administrative and functional regions in the empirical analyses. Data on employment and plant size for the years 1991 and 2001 are used to identify sectoral location patterns in Italy and The Netherlands within the manufacturing and service sectors.
Keywords: 330